Digital Knowledge Systems and Islamic Epistemology: Artificial Intelligence Adoption in Pesantren Education - Yeni Tri Nur Rahmawati; Hamdanah Hamdanah; Suheri Suheri; Wildan Miftahussurur (FALASIFA : Jurnal Studi Keislaman, 2026)
The integration of artificial intelligence (AI) into educational systems has accelerated the transformation of knowledge production, access, and governance across institutional settings. While extensive research has examined the technological and pedagogical impacts of AI in education, limited studies have explored how AI adoption interacts with educational institutions grounded in religious epistemological traditions. This study investigates the dynamics of digital knowledge systems, Islamic epistemology, and artificial intelligence adoption in pesantren education. The research focuses on how AI technologies are implemented in learning and administrative processes, how they influence patterns of knowledge accessibility, and how institutional governance responds to the emergence of algorithmically mediated knowledge environments. Using a qualitative institutional approach, data were collected through interviews, document analysis, and field observations in selected pesantren institutions undergoing digital transformation. The findings indicate that AI adoption enhances learning accessibility, instructional efficiency, and administrative effectiveness while simultaneously generating a hybrid knowledge environment in which digital information systems coexist with teacher-centered interpretive authority. The study highlights that sustainable AI integration depends on leadership commitment, governance frameworks, and digital literacy development to ensure responsible and context-sensitive technology utilization.